New Perspectives on Diagnosis and Therapy of Malignant Pleural Mesothelioma - Rossini, Marika; Rizzo, Paola; Bononi, Ilaria; Clementz, Anthony; Ferrari, Roberto; Martini, Fernanda; Tognon, Mauro G. (Frontiers in Oncology, 2018)
Malignant pleural mesothelioma is a rare, but severe form of cancer, with an incidence that varies significantly within and among different countries around the world. It develops in about one to two persons per million of the general population, leading to thousands of deaths every year worldwide. To date the malignant pleural mesothelioma is mostly associated with occupational asbestos exposure. Asbestos represents the predominant etiological factor, with approximately 70% of cases of malignant pleural mesothelioma with well documented occupational exposure to asbestos, with the exposure time, on average greater than forty years. Environmental exposure to asbestos is increasingly becoming recognized as a cause of mesothelioma, together with gene mutations. The possible roles of other co-factors, such as viral infection and radiation exposure are still debated. Malignant pleural mesothelioma is a fatal tumor. This cancer arises during its early phase without clinical signs. Consequently, its diagnosis occurs at advanced stages. Standard clinical therapeutic approaches include surgery, chemo- and radio-therapies. Preclinical and clinical research are making great strides in the field of this deadly disease, identifying new biomarkers and innovative therapeutic approaches. Among the newly identified markers and potential therapeutic targets, circulating microRNAs and the Notch pathway represent promising avenues that could result in the early detection of the tumor and novel therapeutic approaches.